Representation of Social Harmonization in The Film Get Married - Mohammad Iqbal Maulana; Rezki Rahmawati; Dewi Nuraliah; Nurfadilah Nasiruddin (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Indonesia as a plural country, the identity of the people varies from ethnicity to social structure, so social harmonization discourse is a topic of achievement in its society. Film is one of the media in reproducing the representation of a reality. In movies, reality comes through codes, symbols, and symbols.  This study aims to describe the reality of social harmonization present in the film Get Married. This research is qualitatively descriptive and semiotic analysis methods from Roland Bhartes, in semiotics Barthes divides three stages namely denotation, connotation, and myth.  The results of the analysis of social harmonization messages in the film Get Married, denotationally harmonized messages are often represented in the form of respect, happiness, joyful laughter, even the impression of sadness always ends with happiness, social harmonization attitudes are always interpreted with pleasure and happiness. Connotation of social harmony representation is shown how to foster social relations that have a variety of different community backgrounds between upper and lower class groups, it is represented through dimensions such as coding clothes and also gestures between the two different groups, but can foster social harmonization, and myths refer to the culture of hospitality and politeness as capital in establishing social harmony,  Despite the social gap in identity, a culture of hospitality and courtesy has always been key to social harmony.